2002
DOI: 10.1111/1540-6261.00419
|View full text |Cite
|
Sign up to set email alerts
|

Venture Capital and the Professionalization of Start‐Up Firms: Empirical Evidence

Abstract: This paper examines the impact venture capital can have on the development of new firms. Using a hand-collected data set on Silicon Valley start-ups, we find that venture capital is related to a variety of professionalization measures, such as human resource policies, the adoption of stock option plans, and the hiring of a marketing VP. Venture-capital-backed companies are also more likely and faster to replace the founder with an outside CEO, both in situations that appear adversarial and those mutually agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
512
2
7

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,701 publications
(541 citation statements)
references
References 26 publications
20
512
2
7
Order By: Relevance
“…Lerner and Avrahami (2002) Several studies have reported important value added benefits provided by venture capitalists. These benefits include help in obtaining additional financing, improving investment decisions and providing non-financial assistance such as strategic planning and help in recruiting key executives (MacMillan et al, 1989;Gorman and Sahlman, 1989;Sapienza, 1992;Goupta and Sapienza, 1992;Sapienza et al, 1996;Hellman and Puri, 2001). Recent research on the VC investment decision process suggests that VCs lack a strong understanding of how they make decisions.…”
Section: Financementioning
confidence: 99%
“…Lerner and Avrahami (2002) Several studies have reported important value added benefits provided by venture capitalists. These benefits include help in obtaining additional financing, improving investment decisions and providing non-financial assistance such as strategic planning and help in recruiting key executives (MacMillan et al, 1989;Gorman and Sahlman, 1989;Sapienza, 1992;Goupta and Sapienza, 1992;Sapienza et al, 1996;Hellman and Puri, 2001). Recent research on the VC investment decision process suggests that VCs lack a strong understanding of how they make decisions.…”
Section: Financementioning
confidence: 99%
“…For example, companies such as Adobe, AMD, Intel, Cisco Systems, Electronic Arts, Oracle, Sun Microsystems, Yahoo!, and Google raised funding at their seed stage from VC firms. Start-ups funded by institutional VC investors usually have a faster growing business (Hellman & Puri, 2002), create numerous jobs, and have an important impact on the business environment. These facts justify research on the VC industry even if VC firms only represent a limited source of funding at the seed stage of start-ups.…”
Section: Introductionmentioning
confidence: 99%
“…The lead investor develops social ties with the entrepreneur prior to investment. After closing the funding, he or she becomes strongly involved in the management of the start-up (Brander, Amit, & Antweiler, 2002;Hellman & Puri, 2002;Hsu, 2004;Lerner, 1995;Sapienza, 1992). Generally, he or she is on the board of directors of the invested company.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It specializes in financing and nurturing companies at an early stage of development ('start-ups') that operate in high-tech industries. For these companies the expertise of the venture capitalist, its knowledge of markets and of the entrepreneurial process, and its network of contacts are most useful to help unfold their growth potential (Bottazzi, Da Rin and Hellmann (2005a), Gompers (1995), Hellmann and Puri (2002), and Lerner (1994Lerner ( , 1995). By contrast, when venture capital is applied to companies at a later stage of their growth, or in companies which operate in technologically mature industries, it has less of an opportunity to 'make a difference' (Michelacci and Suarez (2004)).…”
Section: Introductionmentioning
confidence: 99%